2018
DOI: 10.15376/biores.13.3.6480-6496
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of zinc oxide nanoparticle-treated kenaf polymer composites for weather resistance based on a solar UV radiation

Abstract: Polyester/kenaf composites reinforced with zinc oxide nanoparticles (ZnO NPs) were fabricated. The nanoparticle treatment had a noticeable effect on the mechanical properties of the composites. Kenaf treatments with five different concentrations 1%, 2%, 3%, 4%, and 5% were performed. The mechanical analysis showed an increased flexural strength stability and break elongation in the functionalized ZnO NPs-treated kenaf polyester resin composites. The polymer nanocomposites with 2% ZnO NPs had stable mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Anoop et al (2009) investigated the effect of different nanoparticle sizes on the heat transfer, observing that the nanofluids have high heat transfer capacity. Mohammed et al (2018) used ZnO nanoparticles on wood composites to improve weather resistance and better physical and mechanical properties. In addition, Bak and Németh (2018) verified that zinc oxide provides effective protection against fungi, showing good protection for both investigated fungi, Coniophora puteana and Coriolus versicolor.…”
Section: Cardoso Et Al (2016)mentioning
confidence: 99%
“…Anoop et al (2009) investigated the effect of different nanoparticle sizes on the heat transfer, observing that the nanofluids have high heat transfer capacity. Mohammed et al (2018) used ZnO nanoparticles on wood composites to improve weather resistance and better physical and mechanical properties. In addition, Bak and Németh (2018) verified that zinc oxide provides effective protection against fungi, showing good protection for both investigated fungi, Coniophora puteana and Coriolus versicolor.…”
Section: Cardoso Et Al (2016)mentioning
confidence: 99%
“…This was not in agreement with Kareem et al, whose findings showed that the efficiency of ZnONPs against multidrug-resistant bacteria is higher compared with that of AgNPs. Mohammad et al reported that ZnONPs were effective against Klebsiella pneumonia , Listeria monocytogenes , and Salmonella enteritidis pathogens. The chemically synthesized silver nanoparticles have proven to inhibit the studied pathogenic organisms used for the study, though zinc oxide nanoparticles only inhibited Gram-positive organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Various surface treatment procedures such as alkylation, acetylation, and maleated coupling have been used to promote the compatibility of the matrix and NFr. NPs or nanofillers offer enormous potential for usage as filler materials in polymer composites to improve their qualities (Mohammed et al 2018). Academics and researchers have improved the characteristics of NFr reinforced polymer composites by including nano clay, nano-silica SiO2, carbon nanotubes, and a variety of other NPs (Mohammed et al 2017a, b).…”
Section: Nanoparticle Treatment Natural Fibre Polymer Compositesmentioning
confidence: 99%
“…The interfacial characteristics can be improved by modifying the fibre, matrix, and NPs in hybrid composites (Pracella et al 2010). NPs is considered to increase the surface roughness of the fibre, hence increasing interfacial adhesion by mechanical interlocking (Mohammed et al 2018).…”
Section: Nanoparticle Treatment Natural Fibre Polymer Compositesmentioning
confidence: 99%